High prevalence of exercise-induced stridor during Parkrun: a cross-sectional field-based evaluation. Issue 1 (30th September 2020) - Sails, Joe; Hull, James H; Allen, Hayden; Darville, Liam; Walsted, Emil S; Price, Oliver J
Abstract : Background and objective: The differential diagnosis for exercise-associated breathlessness is broad, however, when a young athletic individual presents with respiratory symptoms, they are most often prescribed inhaler therapy for presumed exercise-induced asthma (EIA). The purpose of this study was therefore to use a novel sound-based approach to assessment to evaluate the prevalence of exertional respiratory symptoms and characterise abnormal breathing sounds in a large cohort of recreationally active individuals. Methods: Cross-sectional field-based evaluation of individuals completing Parkrun. Phase 1: Prerace, clinical assessment and baseline spirometry were conducted. At peak exercise and immediately postrace, breathing was monitored continuously using a smartphone. Recordings were analysed retrospectively and coded for signs of the predominant respiratory noise. Phase 2: A subpopulation that reported symptoms with at least one audible sign of respiratory dysfunction was randomly selected and invited to attend the laboratory on a separate occasion to undergo objective clinical workup to confirm or refute EIA. Results: Forty-eight participants (22.6%) had at least one audible sign of respiratory dysfunction; inspiratory stridor (9.9%), expiratory wheeze (3.3%), combined stridor+wheeze (3.3%), cough (6.1%). Over one-third of the cohort (38.2%) were classified as symptomatic. Ten individuals attended a follow-up appointment, however, only one had objective evidence of EIA. Conclusions: The most common audible sign, detected in approximately 1 in 10 individuals, was inspiratory stridor, a characteristic feature of upper airway closure occurring during exercise. Further work is now required to further validate the precision and feasibility of this diagnostic approach in cohorts reporting exertional breathing difficulty.